Simulation and team training embedded nurse mentoring programme and improvement in intrapartum and newborn care in a low-resource setting in Bihar, India - Ghosh, Rakesh; Spindler, Hilary; Dyer, Jessica; Christmas, Amelia; Cohen, Susanna R; Das, Aritra; Sonthalia, Sunil; Mahapatra, Tanmay; Gore, Aboli; Shah, Hemant; Walker, Dilys M (Journal of global health, 2020)
Improvement of the quality of maternal and child health care remains a focus in India. Working with the Government of Bihar, CARE-India facilitated a comprehensive set of quality of care improvement initiatives. PRONTO's simulation and team-training was incorporated into the large-scale (AMANAT)nurse-mentoring program of the Government of Bihar supported by CARE-India to improve maternal and child health outcomes. Along-with the AMANAT program, the PRONTO components provided training on nontechnical and technical competencies for managing a variety of obstetric and neonatal conditions, as a team. This study assessed the effectiveness of nurse-mentoring including simulations on intrapartum and newborn care practices in 320 basic emergency obstetric and neonatal care (BEmONC) facilities. Deliveries were observed to obtain specific information on evidence-based practice (EBP) indicators before and after the intervention. Intrapartum and newborn care composite scores - were calculated using those EBP indicators. A web-based routine monitoring system provided total training days, weeks and days/week of training and counts of simulation and teamwork-communication activities. Multilevel linear regression was used to examine the exposure-outcome associations. The final analysis included 668 normal spontaneous vaginal deliveries (NSVDs) from 289 public health facilities in Bihar. Facility-level intrapartum and newborn scores improved by 37 and 26-percentage points, respectively, from baseline to endline. Compared to the bottom one-third facilities that performed fewest NSVD simulations, the top one-third had 6 (95% confidence interval (CI) = 1-12) percentage points higher intrapartum score. Similar comparison using maternal complication simulations yielded 7 (95% CI = 1-12) percentage point higher scores. The highest newborn scores were observed in the middle one-third of facilities relative to the bottom one-third that did the fewest NSVD simulations (5, 95% CI: 1-10). Findings suggest significant overall improvement in intrapartum and newborn care practices after the AMANAT nurse-mentoring program in public sector BEmONC facilities. Simulation and team-training likely contributed towards the overall improvement, especially for intrapartum care. ClinicalTrials.gov number NCT02726230.